Выражение ! (x-1)(x-2)(x++1)(x+2)(x-3) только неисполнительность просто ответ, а !

куликов44443456 куликов44443456    2   14.08.2019 18:40    0

Ответы
syune333 syune333  04.10.2020 19:22
(x-1)(x-2)(x+3)-(x+1)(x+2)(x-3)=(x²-3x+2)(x+3)-(x²+3x+2)(x-3)=x³-3x²+2x+3x²-9x+6-x³+3x²-3x²+9x-2x+6=12
ПОКАЗАТЬ ОТВЕТЫ
georgijandreev1 georgijandreev1  04.10.2020 19:22
(х-1)(х-2)(х+3)-(х+1)(х+2)(х-3)=(x^2-2x-x+2)(X+3)-(x^2+2X+X+2)(x-3)=x^3-3x+2X+3x^2-9x+6-(x^3+3X+2x-6x-3x-6=x^3-3x^2+2X+3x^2-9x+6-x^3-3x^2-2x+6X+3X+6=-3x^2+12 Можно решать дальше вот так -3x^2=-12 x^2=4 χ=+-2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика